Polycystic ovary syndrome and the risk of endometrial, ovarian and breast cancer: An updated meta-analysis. Issue 3 (August 2022) - Li, Zhen; Wang, Yu-Hua; Wang, Lin-Lin; Hu, Ding-Tao; Teng, Ying; Zhang, Ting-Yu; Yan, Zi-Ye; Wang, Fang; Zou, Yan-Feng
Background and Aims: This updated meta-analysis aimed to further quantify the risk of endometrial, ovarian, and breast cancer in patients with polycystic ovary syndrome (PCOS), thus providing updated and more reliable estimates. Methods and Results: We identified relevant articles by searching electronic databases of PubMed, Embase, Web of Science, and Chinese Biological Medical Literature (CBM) published up to March 20, 2021. The pooled effect estimates and their 95% confidence intervals ( CIs ) were calculated using the random-effect model or the fixed-effect model. A total of 26 eligible studies were included. We found that PCOS was significantly associated with endometrial cancer (odds ratios [ OR ]: 3.66, 95% CI : 2.05–6.54, P  < 0.001), but not with ovarian or breast cancer ( OR : 1.23, 95% CI : 0.99–1.53, P  = 0.059; OR : 0.94, 95% CI : 0.78–1.14, P  = 0.551, respectively). However, in subgroups of high-quality studies, cohort studies, younger women (54 years or less or premenopausal), and studies with unadjusted body mass index (BMI), PCOS patients had a significantly higher risk of ovarian cancer. Conclusion: These results indicated that PCOS is a significant risk factor for endometrial cancer independent of BMI, but not for breast cancer. PCOS may increase the risk of ovarian cancer in younger women.